Respostas
respondido por:
10
x² – 4x ≥ 0.
Temos que as raízes da equação são 0 e 4.Assim,sendo f(x)=x² – 4x,temos que:
I.f(x)=0 para x=0 ou x=4;
II.f(x) < 0 ,∀x ∈ (0,4);
III.f(x) > 0 , ∀x (x < 0 ou x> 4)
Então,a solução da inequação é:
S={x ∈ R/ x ≤ 0 ou x ≥ 4}
Temos que as raízes da equação são 0 e 4.Assim,sendo f(x)=x² – 4x,temos que:
I.f(x)=0 para x=0 ou x=4;
II.f(x) < 0 ,∀x ∈ (0,4);
III.f(x) > 0 , ∀x (x < 0 ou x> 4)
Então,a solução da inequação é:
S={x ∈ R/ x ≤ 0 ou x ≥ 4}
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás